10.1515/pz-2014-0014 (CrossRef Listing of Deleted DOIs, 2015)
OBJECTIVES: This study aimed to investigate the role of Human Leukocyte Antigen-G (HLA-G) gene expression, inflammatory cytokines, and hormonal profiles in the pathogenesis of recurrent pregnancy loss (RPL) and to assess their potential as diagnostic and predictive markers. METHODS: A case-control study was conducted involving 240 women, including 120 with clinically confirmed RPL and 120 fertile controls. Serum levels of CRP (C-reactive protein) and IL-6 (interleukin-6) were measured using enzyme-linked immunosorbent assay (ELISA). Hormonal parameters, including thyroid-stimulating hormone (TSH), follicle-stimulating hormone (FSH), and luteinizing hormone (LH), were analyzed using chemiluminescence immunoassays (CLIA). HLA-G gene expression was quantified using quantitative real-time polymerase chain reaction (qRT-PCR). Statistical analyses included t-tests, receiver operating characteristic (ROC) curve analysis, and logistic regression to identify independent predictors. RESULTS: RPL cases showed significantly higher levels of TSH, FSH, CRP, and IL-6 and markedly lower HLA-G gene expression compared with controls (p < 0.001). CRP showed the highest diagnostic accuracy (AUC = 0.997), followed by HLA-G (AUC = 0.938) and IL-6 (AUC = 0.896). Logistic regression identified IL-6, FSH, TSH, and HLA-G as independent predictors of RPL. CONCLUSIONS: The findings highlight the interplay between immune dysfunction, hormonal imbalance, and reduced HLA-G expression in RPL. These markers may help in the early identification and risk assessment of RPL, with HLA-G showing potential for further investigation as a therapeutic target.